2020
DOI: 10.1021/acsami.0c17568
|View full text |Cite
|
Sign up to set email alerts
|

Design of the Enzyme–Carrier Interface to Overcome the O2 and NADH Mass Transfer Limitations of an Immobilized Flavin Oxidase

Abstract: Understanding how the immobilization of enzymes on solid carriers affects their performance is paramount for the design of highly efficient heterogeneous biocatalysts. An efficient supply of substrates onto the solid phase is one of the main challenges to maximize the activity of the immobilized enzymes. Herein, we apply advanced single-particle analysis to decipher the optimal design of an immobilized NADH oxidase (NOX) whose activity depends both on O 2 and NADH concentrations. Carrier physicochemical proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 33 publications
(64 citation statements)
references
References 50 publications
8
47
0
Order By: Relevance
“…This effect might be the result of a faster incubation with the enzyme (1 h) that promotes only the ionic adsorption of the enzyme on the outer surface of the PEI‐lignin. These results are in agreement with previously reported studies where enzymes immobilized predominantly on the exposed surface of the support (as opposed to those that diffuse through the porous matrix) display a higher activity due to better mass transfer ability from the bulk to the catalyst [33–35] . However, more sophisticated studies would be needed to decipher the exact effect observed.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…This effect might be the result of a faster incubation with the enzyme (1 h) that promotes only the ionic adsorption of the enzyme on the outer surface of the PEI‐lignin. These results are in agreement with previously reported studies where enzymes immobilized predominantly on the exposed surface of the support (as opposed to those that diffuse through the porous matrix) display a higher activity due to better mass transfer ability from the bulk to the catalyst [33–35] . However, more sophisticated studies would be needed to decipher the exact effect observed.…”
Section: Resultssupporting
confidence: 92%
“…To avoid undesired hydrophobic interactions during enzyme immobilization, several additives (ethanol, SDS, glycerol, triton) were trialed during the immobilization process [35,36] . Nevertheless, no significant improvements over the resulting activity (U g −1 ) of the biocatalyst were detected (Figure S7).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations